Personalizing Self-Management Interventions in COPD – Looking Beyond One-Size-Fits-All - Lenferink A; Brusse-Keizer MG; van der Palen J; Effing TW (International Journal of COPD)
Anke Lenferink,1,2 Marjolein GJ Brusse-Keizer,1,3 Job van der Palen,3,4 Tanja W Effing5,6 1Health Technology and Services Research, Faculty of Behavioural, Management and Social Sciences, Technical Medical Centre, University of Twente, Enschede, The Netherlands; 2Department of Pulmonary Medicine, Medisch Spectrum Twente, Enschede, The Netherlands; 3Medical School Twente, Medisch Spectrum Twente, Enschede, The Netherlands; 4Cognition, Data and Education, Faculty of Behavioural, Management and Social Sciences, University of Twente, Enschede, The Netherlands; 5College of Medicine and Public Health, School of Medicine, Flinders University, Adelaide, Australia; 6School of Psychology, Faculty of Health and Medical Sciences, University of Adelaide, Adelaide, AustraliaCorrespondence: Anke Lenferink, University of Twente Health Technology and Services Research Faculty of Behavioural, Management and Social sciences Technical Medical Centre, P.O. Box 217, 7500, AE Enschede, the Netherlands, Email a.lenferink@utwente.nl